Analysis of the Effect of Premium Income, Underwriting Ratios, Investment Returns, and Claims on Profit Growth in Insurance Companies Listed on the IDX in The 2017-2019 Period - Utami, Dian; Yuliansyah , Yuliansyah (LPPM STIE KRAKATAU, 2025)
This study aims to determine the effect of premium income, underwriting ratio, investment returns, and claims on profit growth. The sampling technique used a purposive sampling method, resulting in a sample of 14 insurance companies that met the criteria. Data analysis techniques used were classical assumption tests, multiple linear regression analysis, coefficient of determination, t-statistical tests, and simultaneous tests. The research results show that premium income and investment returns have a significant positive effect on profit growth. Underwriting and claims ratios did not significantly impact profit growth at insurance companies listed on the IDX in the 2017-2019 period. This study aims to determine the effect of premium income, underwriting ratio, investment returns, and claims on profit growth. The sample consisted of insurance companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The limitations of this study include the presence of outliers that needed to be removed, and the results showed that the independent variables in this study only contributed a small amount to profit growth, namely 33,1%. This research can be used as a reference for further researchers in examining premiums, underwriting ratios, investment returns, and claims in insurance companies.